Otomatis Manual Can Sterilizer Berbasis PLC Omron - Bustanul Arif; Dwi Hadidjaja R.S. (Research Parks Publishing LLC, 2020)
In the industrialized world often encounter the machine equipment is still manually operated or semi-automatic. In their operations in addition to using the command in the form of buttons, selector switches and sensors also need supporting components using either a PLC as the driving force of the machine equipment. Utilizing PLC omron to revamp the system of work that is done manually for upgraded to automatic. So can condense the time and ease of working. To make it more effective and efficient.